Khlopenko N.Y., Sorokina T.N. Turbulent anisothermic lubrication for the Rayleigh step bearing. - Хлопенко, Н.Я.; Сорокина, Т.Н. (Problems of Tribology, 2014)
This article is devoted to the Reyleigh’s step bearing static characteristics analysis at the turbulent anisothermic lubrication. In this type of bearing the pressure gradient is making in time of lubrication charging to the stage pocket under the pressure from the feeding groove. The Reinold’s equation for pressure in the layer, the energy and the oil consumption balance equations were the basis initial systems for a Reyleigh’s step bearing static characteristics determination. Turbulence coefficients were calculated using Constantinescu method for incompressible fluid. The finite difference mesh with a cross scheme was used. The mesh solutions were based on the method of consecutive over relaxation; it gives the possibility to reduce the number of interactions and obtained the required accuracy. The program and the Reyleigh’s step bearing static characteristics calculations were carried out on the basis of above mentioned numerical model. The numerical example shows that the theoretical values of exploring characteristics are well conformed to different scientist test researchers. The turbulence effect was shown to increase the capacity, friction and power losses. The numerical model for the Rayleigh’s step bearing static characteristics analysis at the turbulent anisothermic lubrication is allows carrying out the bearing main factor calculations at the turbulent regime accounting changing the viscosity, temperature and density. The results can become the basic part for the further Reyleigh’s step bearing design for high-speed turbo machines.